Governança privada, governamental e híbrida na Cadeia Global de Valor : considerações a partir do desastre de Brumadinho - Moncada Sánchez, Renato Bernabé (2020)
This research aims to understand how the process of appropriating control of the level of safety of the tailings ore tailings dams in the State of Minas Gerais took place, by private companies and the virtual alienation of the state of this control. This work is part of the ongoing debate on how regulation by the state of the activities of the leading companies in the Global ValueChains (CGV) takes place, in particular on the advantages and disadvantages of private,governmental or hybrid regulation. To achieve this objective, an analysis of an extreme case of control failure and disastrous consequences is carried out, the rupture of the tailings dam at the Córrego do Feijão mine, in Brumadinho. The article represents a relevant theoretical contributionbecause the understanding of how the appropriation process takes place is still incipient in the current debate. Disaster is an extreme and revealing case that provides important data for our definitions. It is intended, as a result of this research, to describe how governance mechanisms are related to the occurrence of disasters. It is hoped that the methods and results of this project can be used in the future as a basis for diagnosing and directing changes in power asymmetries and forms of governance.